PENGARUH KEGIATAN HERBARIUM TERHADAP KEMAMPUAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN DI TK HARAPAN IBU KECAMATAN PENDALIAN IV KOTO KABUPATEN ROKAN HULU - Yelmi Sri Defni; Devi Risma; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to find out the effect of herbarium activities on fine motoric abilities in children aged 5-6 years at TK Harapan Ibu Subdistrict of Pendalian IV Koto, Rokan Hulu Regency. This research is an experimental study using dessain one group design with a pre-test through observation sheets on children's fine motoric abilities. The population in this study were 27 children and the sample in this study was 20 children. The method used is pre-experiment with dessain one group design, which is an experiment carried out in one group without a comparison group. The type of instrument used in this research is to use observation guidelines to record the activities that occur during the treatment given. Based on the results of hypothesis testing obtained on the effect of herbarium activities on fine motoric abilities in children aged 5-6 years at TK Harapan Ibu Subdistrict of Pendalian IV Koto, Rokan Hulu Regency. The test used is the Wilcoxon test. Obtained Z count value of 4,233 with sig 0,000023 because sig <0,05, it can be concluded that there are differences in fine motoric abilities in significant students before and after using herbarium activities. In testing the hypothesis can be seen Z count = 4,233> W table = 3,5. It can be interpreted that there are significant differences in results between pretest and posttest. The effect of herbarium activities on fine motoric abalities in children aged 5-6 years at TK Harapan Ibu Subdistrict of Pendalian IV Koto, Rokan Hulu Regency was 42.16% in the medium category.Key Words: Herbarium Activity, Children's Fine Motoric Ability